2009
DOI: 10.1016/j.ijid.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for brucellosis in Samarqand Oblast, Uzbekistan

Abstract: To reduce the burden of brucellosis in Samarqand Oblast, veterinary services should be improved. Also public health education programs should be increased. Implementing these measures will minimize exposure to infected farm animals and reduce the risk of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 4 publications
5
36
3
1
Order By: Relevance
“…The results, in this regard, are consistent with the findings of Shoraka et al (22), although in a related study in Kurdistan, more patients were housekeepers, with the difference being insignificant (3). In the current study, most cases of the disease occurred in the spring (38.8%) and the lowest rate was in winter (14.9%), percentages which are in agreement with the study by Shoraka et al (22), Sofizadeh et al (21) and the research conducted in Uzbekistan (20,22,29). Nevertheless, the study conducted in Yazd, Iran, revealed that most cases had occurred in the summer (56.5%) (26).…”
Section: Discussionsupporting
confidence: 93%
“…The results, in this regard, are consistent with the findings of Shoraka et al (22), although in a related study in Kurdistan, more patients were housekeepers, with the difference being insignificant (3). In the current study, most cases of the disease occurred in the spring (38.8%) and the lowest rate was in winter (14.9%), percentages which are in agreement with the study by Shoraka et al (22), Sofizadeh et al (21) and the research conducted in Uzbekistan (20,22,29). Nevertheless, the study conducted in Yazd, Iran, revealed that most cases had occurred in the summer (56.5%) (26).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 72.3% of the patients had a history of contact with an animal with brucellosis. This rate is higher than that obtained in Yazd Province (63%), and Babol city, Iran, (54.4%) (17). In our study, 31.11% of the patients had consumed non-boiled (raw) milk and 21.59%, both fresh cheese and non-boiled milk.…”
Section: Discussioncontrasting
confidence: 74%
“…In this study, 44.4% of the morbidity cases occurred in spring, but in the studies conducted in Kashan city and Yazd Province, Iran, most morbidity cases had occurred in the summer (65.5%) (17). In the present study, 72.3% of the patients had a history of contact with an animal with brucellosis.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…These goats may appear apparently healthy but are carriers of the organism thereby increasing the chances of infection greatly at the time of parturition (Garin-Bastuji et al 2006). Assisting in parturition of such infected animals has on several cases been reported to lead to B. melitensis human infection (Earhart et al 2009;Garin-Bastuji et al 2006;Seleem et al 2010). In addition, individuals who clean aborted materials were found to be at higher risk of infection with brucellosis because aborted materials from brucellosis infected animals contain high quantities of the infective bacteria (Chahota et al 2003;Yumuk & O'Callaghan 2012).…”
Section: Discussionmentioning
confidence: 99%